A responsabilidade ética da nutrição frente à questão ambiental - Sipioni, Marcelo Eliseu (2023)
This study is based on the premise that we live in a context of environmental emergency in which human action represents the main geological force on the planet, which configures the theory of the Anthropocene. The prediction that this context puts future generations at risk has mobilized different actors to break this predatory advance of the human being based on new and necessary conceptions about the relationship between humanity and Nature, so that we no longer subject it to the typical instrumental valuation of utilitarian anthropocentrism, defending a conception of belonging to Her, not of superiority. In this sense, the hegemonic food system represents one of the spheres in which this predatory advance takes place, since it uses technologies and production methods that are extremely aggressive towards Nature. This analysis allows us to identify the implication of Nutrition in this topic, since it is a field of knowledge and practices intrinsically related to the logic of food systems, as can be seen from the analysis of what has been called the Global Syndemic. Thus, this study aimed to identify the perception of national leaders in the field of Nutrition in Brazil about the responsibility of Nutrition and nutritionists in relation to the environmental issue. In this way, a descriptive research with a qualitative approach was carried out with the main nutritionist leaders, at the national level, who, during the period of the study, held some management position in professional, academic or public policy entities or agencies in the food and nutrition´s field in Brazil. The leaders were contacted and interviewed by video call during the first half of year 2022. The questions sought to identify perceptions and opinions they had on the environmental issue, in general, and the general challenges in the Nutrition´s field, in addition to requesting that they express their perspectives and analyzes on the real and ideal implication of the Nutrition´s field in Brazil with the current environmental issue. Data were subjected to thematic analysis. Our findings allow us to state that leaders in the field of Nutrition in Brazil recognize the emergence of the environmental issue and the inevitable implication of Nutrition in this context, especially through the logic of food systems. However, they understand as incipient the debate and the actions carried out in this field so that it is inserted, in a qualified way, with the set of actors that seek to reverse the consequences of the destruction of Nature on several fronts. Among the main challenges presented, there is the need for an educational and informative process that allows the defense of an expanded conception of Nutrition, which stimulates reflections beyond the nutritional reductionist logic. In this sense, based on the findings of this research, and based on ethical proposals that move away from utilitarian anthropocentrism, such as Hans Jonas' Principle of Responsibility, we identified the need for Nutrition to reflect on the expansion of the ethical-political assumptions that underlie its field of practices and knowledge, assuming the task of directing the promotion of healthy and adequate food for everyone involved and implicated in the food system, not just for the individual who eats.